Interdecadal Variability of Spring Eurasian Snowmelt and Its Impact on Eastern China Summer Precipitation - Cheng, Fei; Li, Qiaoping; Wang, Jing; Liu, Yanju; Ding, Yihui; Shen, Xinyong; Song, Chengyu (Frontiers in Earth Science, 2022)
In this study, the interdecadal variability of Eurasian spring snowmelt and its relationship with Eastern China summer precipitation (ECSP) are investigated based on observations and reanalysis data. Results show that the second mode of the empirical orthogonal function (EOF) analysis of the spring snowmelt, featured as a west-east dipole pattern, displays two interdecadal changes near the late-1970s and in the mid-2000s. The increased spring snowmelt over the Western Siberia (WSI) and the opposite situation over the Eastern Europe (EEU) are significantly linked to a meridional quadrupole summertime rainfall pattern on interdecadal time scales, with excessive rainfall over the regions of southern China (SC) and the Huang-Huai River (HHR) and deficient rainfall over the middle and lower reaches of Yangtze River Valley (YRV) and Inner Mongolia-northeastern China (IMNC). Besides, the possible mechanisms are discussed from the perspective of the hydrological effect related to snowmelt-induced soil moisture. Increased spring snowmelt can produce more water inflowing into the soil, leading to anomalous soil moisture, which can persist into summer. Excessive (deficient) snowmelt-related soil moisture anomalies over the WSI (EEU) in summer will change local land thermal conditions and thus generate cyclonic (anticyclonic) circulations with a quasi-barotropic structure. Therefore, the eastward-propagating wave-activity flux (WAF) could be strengthened over the WSI and EEU in the mid- and upper-troposphere and further propagate downstream, leading to an anomalous anticyclonic (cyclonic) circulation near the Lake Baikal (SC) and the related strong descending (ascending) motion over the IMNC (SC). Meanwhile, strong positive (negative) upper-level divergence appears over the YRV (HHR), which is the right (left) side of the exit region of upper-level jet. The upper-level divergence could be attributed to the convergence (divergence) of meridional winds on the right side of the anticyclonic circulation. As a result, the uniform descending (ascending) motion also appears over the YRV (HHR) through the collocation of upper-level convergence(divergence) and the compensatory lower-level circulations. Consequently, a quadrupole pattern of secondary circulation over Eastern China is founded, thereby causing the anomalously distributed ECSP under favorable water vapor conditions.